Effect of Moringa Oleifera on Tumor Necrosis Factor-Alpha and Extracellular Matrix Trabecular Meshwork of Glaucoma Model Wistar Rats - Maharani, Maharani; Astuti, Ratih Kusuma; Rahmi, Fifin Luthfia; Prihatningtias, Riski; Istiadi, Hermawan; Wildan, Arief (Journal of Biomedicine and Translational Research, 2025)
Background: Elevated intraocular pressure (IOP) induces inflammation in the trabecular meshwork (TM) through increases in tumor necrosis factor-alpha (TNF-α) expressions by activating nuclear factor kappa B (NF-κB). Mechanical injury to the TM, such as increased IOP, can cause extracellular matrix (ECM) remodeling, impacting the permanent outflow of aqueous humor. Moringa oleifera (MO) leaf extract is an anti- inflammatory agent that inhibits NF-κB activation and has been studied to have antioxidant effects.Objective: to analyze the effects of MO leaf extract on TNF- α expression and the thickness of the trabecular meshwork ECM in a Wistar rat glaucoma model. Methods: Fourteen male Wistar rats were divided into two groups (n=7): the glaucoma group received oral MO leaf extract at 300 mg/kg body weight for four weeks, and the control group. TNF-α expressions were measured by immunohistochemical stain, and the thickness of the ECM was examined with hematoxylin eosin staining. P-values of less than 0.05 were considered to represent statistical significance.Results: The mean of TNF-α expressions in the treatment group was 4.29 ± 0.76, and the control group was 5.29 ± 0.49. There was a significant difference in TNF-α expressions between the two groups (p=0.015). The mean thickness of the ECM TM experimental group and control group were 155.65 ± 28.72μm and 218.63 ± 40.85μm respectively. The extracellular matrix TM experimental group was statistically significantly thinner than the control group (p=0.006).Conclusion: MO could protect TM from damage caused by high IOP by suppressed TNF- α expression and ECM thickness in the TM Wistar glaucoma model.